Enhancing the Primary Students’ 21st Century Learning Skills through the Curriculum Integration - Banpho, Thuwanon; Jongkonklang, Sirinat; Keeratichamroen, Wasana (Ratchaphruek Journal, 2019)
This paper presents the investigation of the development and the evaluation of the primary school curriculum which integrated the 21st century learning skills. It was found that there are three stages of developing of the curriculum : first, the preparation of the curriculum stage, second, the development of the curriculum stage and third, the trial, evaluation and improvement of the curriculum stage. The core parts of curriculum should consist of objective, content, learning activity, and assessment. Thus, the 21st century learning skills consist of reading, writing, arithmetic, critical thinking and problem, creativity and innovation, cross-cultural understanding, collaboration teamwork and leadership, communications information and media literacy, computing and ICT literacy, career and learning skills, and compassion. They should be merged in every part of the curriculum. The results showed that the level of students’ ability toward the 21st century learning skills was high. Thus, it was concluded that the curriculum which integrated with the 21st century learning skills was suitable for teaching and learning in primary school.